Upaya Peningkatan Pengetahuan dan Edukasi Tentang Anemia pada Remaja - Ernawati, Evy; Sari, Fatimah; Heldayasari, Febry; Intan Navelia, Zesika; Merida, Yunri; Hanifa, Fatya Nurul (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2025)
Background: Iron-deficiency anemia (IDA) is a significant health problem among adolescents, especially in Indonesia. The prevalence of iron deficiency anemia in children in Indonesia reached 28.1% according to Riskesdas in 2018. Low knowledge and inadequate iron intake are the main factors causing this anemia. This can have an impact on their health and learning ability. Anemia in adolescent girls can cause fatigue, decreased concentration, and impaired growth and development. Health education plays an important role in improving schoolgirls' knowledge about anemia, the importance of iron, and how to take Fe tablets correctly. Objective: This community service aims to analyze the effect of providing health education about IDA on the knowledge level of female students of SD N 3 Tlogowatu. Methods: questionnaires and lectures. Results: The pretest and posttest results of schoolgirls' knowledge about the effect of Fe tablet consumption on anemia increased to 94%. Conclusion: Increased knowledge is expected to increase awareness and compliance of schoolgirls in taking good nutritions and also suplementation such Fe tablets, thus contributing to the prevention and control of IDA. Suggestion: this is expected to contribute to improving the health and quality of life of primary school students, as well as provide a basis for the development of more effective health education programs.